ESKATOLOGI ISLAM DALAM AL-QUR’AN: Studi I‘jāz Balāgī atas Ayat-ayat Eskatologi - Inayah, Ridotul (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2022)
The problem related to the fundamental teachings of Islamic theology is that the concept of eschatology is considered something impossible to occur because it is beyond human reason and experience, leading people to deny their faith in it. Efforts to address this issue involve delving deeper by referring to the Quran through the study of balāgah al-Qur’ān or i’jāz balāgī. This article analyzes how the interpretation of i‘jāz al-balāgī in eschatological verses is perceived by exegetes. The research design used is descriptive analysis with a literature review method and a qualitative approach. The results of this study show that the description of Islamic eschatological concepts in the Quran is abundant and clear. The entire balāgī aspects covering eschatological verses produce a literary style that is dense and beautiful, resulting in meanings that have a strong persuasive effect. Therefore, human faith in the concept of eschatology must be reconstructed and believed as part of the theological teachings, substantiated by the practice of taqwa.